FAKTOR – FAKTOR YANG MENDORONG DIPERGUNAKANNYA BENTUK USAHA PERSEKUTUAN KOMANDITER DIBANDINGKAN DENGAN FIRMA DALAM PRAKTEK DI SAMARINDA - Edi Amad (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTFactors - factors that encourage entrepreneurs to choose the form of business partnership firm Commanditaire compared with the practice in the city of Samarinda is as follows: younger Kommandit gesellschaft raise capital by issuing shares - shares, while the firm it can not be done; Kommanditgesellschaft may consist of one person, while the alliance with the Firm must consist of more than one person; In partnership with the firm usually from family members, while the Kommandi tgesellschaft outsider can become a member so mulunya can be assured; Clear division of labor among the allies, because of the different motivations among them, so clearly the responsibility of each - each member, then as a result be controlled with good management. While the barriers - barriers that exist in a firm alliance with each partner are as follows: The environment of limited partner or not extensive; In alliance with a firm ally of the role of capital and the role into one that can not be separated between board members that include capital; Responsibility to bear the responsibility (Article 18 businesses).